Talking Therapies in a specialist community diabetes service: Helping people to live with diabetes. (2022) - Heald, Adrian; Horne, Linda; Metters, Ann; Steele, Tom; Moreno, Gabriela Y Cortes; Simms, Ella
No abstract available